Pengembangan Modul Interaktif Pembelajaran Biologi Berbasis Discovery Learning untuk Meningkatkan Keterampilan Berpikir Kreatif pada Materi Sistem Ekskresi di SMA - Zahraa Zalikha; Efrida Pima Sari Tambunan (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to develop an interactive Biology module based on Discovery Learning on the Excretory System topic for eleventh-grade students and to evaluate its validity, practicality, and effectiveness in improving creative thinking skills. The method used was Research and Development (R&D) using the 4D model, involving 26 eleventh-grade students, expert validation sheets, teacher and student response questionnaires, and essay tests based on creative thinking indicators, with data analyzed using Likert scales, percentages, and N-Gain. The findings revealed that the developed module was highly valid, practical for classroom use, and capable of improving students' creative thinking skills. Conclusion, the Discovery Learning-based interactive module is feasible and effective as a learning resource for the excretory system topic and supports the development of creative thinking skills. Keywords: Creative Thinking Skills, Discovery Learning, Excretory System, Interactive Module